Definitive Hosts of Versteria Tapeworms (Cestoda: Taeniidae) Causing Fatal Infection in North America - Laura M. Lee (Emerging Infectious Diseases, 2016)
We previously reported fatal infection of a captive Bornean orangutan with metacestodes of a novel taeniid tapeworm, Versteria sp. New data implicate mustelids as definitive hosts of these tapeworms in North America. At least 2 parasite genetic lineages circulate in North America, representing separate introductions from Eurasia.